Ayat-ayat Sains dalam al-Quran (Telaâah Bala>ghah) - FATIMAH, FATIMAH (Jurnal al Hikmah, 2017)
Balaghah in the Quran is the only aspect of the miracles even on every verse, every sentence or words. Furthermore, that miracle of the balaghah is also present in the element on every letters of the words. The verses of science in the Qurâan is interesting to be studied from balaghah aspect because this effort is like digging and revealing information science in verses of the Qurâan by literary side or from the beauty and accuracy of the Qurâan language structure in giving information of the science. Literature and science are two unique things when linked in understanding the meaning of Qurâan. Considering the verses of science in the Qurâan is not little, so this paper just only takes the examples from some verses, they are the formation of this universe and this earth, the sun is shining, the moon is glowing, the mountains are moving, the process of human events, and the last is about human reproduction.